Switch of phosphorylation to O-GlcNAcylation of AhR contributes to vascular oxidative stress induced by benzo[a]pyrene - Rong Wang; Yun Huang; Xiaoruo Gan; Chenghao Fu; Yuemin Li; Ning Chen; Hao Xi; Huishan Guo; Wei Zhang; Yuhong Lü; Yan Zhang; Pin Lü (Food Science and Human Wellness)
Benzo[a]pyrene (B[a]P) is a food contaminant toxic for cardiovascular diseases. The nuclear translocation of Arylhydrocarbon receptor (AhR) plays an important role in B[a]P-induced oxidative stress and vascular diseases. We confirmed that B[a]P promoted ROS production in vascular smooth muscle cells (VSMCs) in vitro and in vivo, associated with the nuclear translocation of AhR. It is known that phosphorylation inhibits while dephosphorylation of AhR promotes nuclear translocation of AhR. However, from the posttranslational modification level, the mechanism by which B[a]P activates and regulates the nuclear translocation of AhR is unclear. Co-immunoprecipitation results showed that cytoplasmic AhR was phosphorylated before B[a]P stimulation, and switched to O-GlcNAcylation upon B[a]P 1-h stimulation in VSMCs, suggesting there may be a competitively inhibitory relationship between O-GlcNAcylation and phosphorylation of AhR. Next, siRNAs of O-linked N-acetylglucosamine transferase (OGT), O-GlcNAcase (OGA) and OGA inhibitor PUGNAc were used. SiOGT blocks but siOGA and PUGNAc promote B[a]P -dependent AhR nuclear translocation and oxidative stress. Ser11 may be the competitive binding site for phosphorylation and O-GlcNAcylation of AhR. Phosphorylation-mimic variant inhibits but O-GlcNAcylation of AhR promotes AhR nuclear translocation and oxidative stress. Our findings highlight a new perspective for AhR nuclear translocation regulated by the competitive modification between phosphorylation and O-GlcNAcylation.